Characteristics of Cd accumulation and distribution in two sweet potato cultivars. Issue 4 (21st March 2019) - Huang, Baifei; Dai, Hongwen; Zhou, Wenjing; Peng, Lijing; Li, Meizhen; Wan, Renjie; He, Wenting
Abstract: In this study, we compared the chemical forms and subcellular distribution of Cd in high-Cd (X16) and low-Cd (N88) sweet potato cultivars through hydroponic experiments and examined the Cd distribution in their roots by histochemical staining. The results showed that inorganic and pectate/protein-integrated Cd predominated in the leaves, and Cd concentrations were significantly higher in X16 than in N88. However, in the roots, Cd was mostly integrated with pectate and protein, and Cd concentration was higher in N88 than in X16. It was mainly stored through vacuolar sequestration and cell wall binding. In the leaves and stems, Cd concentrations in all subcellular fractions were higher in X16 than in N88; the opposite was observed in the roots. In X16, Cd was mostly accumulated in the root stele, and its Cd translocation factor was higher than that of N88. Overall, the subcellular fractions of X16 roots retained less Cd than N88 roots, and more Cd entered the root stele of X16 and subsequently moved to the shoots. The higher amounts of inorganic, water-soluble, and pectate/protein-integrated Cd with high mobility in the shoots of X16 than in N88 might facilitate Cd remobilization to other tissues, but this needs to be further studied.